Capturing Information Needs of Care Providers to Support Knowledge Sharing and Distributed Decision Making - Rogers, M.; Zach, L.; An, Y.; Dalrymple, P. (Applied Clinical Informatics, 2012)
Background: This paper reports on work carried out to elicit information needs at a trans-disciplinary, nurse-managed health care clinic that serves a medically disadvantaged urban population. The trans-disciplinary model provides a “one-stop shop” for patients who can receive a wide range of services beyond traditional primary care. However, this model of health care presents knowledge sharing challenges because little is known about how data collected from the non-traditional services can be integrated into the traditional electronic medical record (EMR) and shared with other care providers. There is also little known about how health information technology (HIT) can be used to support the workflow in such a practice.Objectives: The objective of this case study was to identify the information needs of care providers in order to inform the design of HIT to support knowledge sharing and distributed decision making.Methods: A participatory design approach is presented as a successful technique to specify requirements for HIT applications that can support a trans-disciplinary model of care.Results: Using this design approach, the researchers identified the information needs of care providers working at the clinic and suggested HIT improvements to integrate non-traditional information into the EMR. These modifications allow knowledge sharing among care providers and support better health decisions.Conclusions: We have identified information needs of care providers as they are relevant to the design of health information systems. As new technology is designed and integrated into various workflows it is clear that understanding information needs is crucial to acceptance of that technology.
Keywords: Information needs; participatory design; requirements analysis and design; clinical information technology; nursing workflow; provider-provider communications